2009
DOI: 10.1074/jbc.m808641200
|View full text |Cite
|
Sign up to set email alerts
|

7-Ketocholesterol Incorporation into Sphingolipid/Cholesterol-enriched (Lipid Raft) Domains Is Impaired by Vitamin E

Abstract: Cholesterol oxides, in particular 7-ketocholesterol, are proatherogenic compounds that induce cell death in the vascular wall when localized in lipid raft domains of the cell membrane. Deleterious effects of 7-ketocholesterol can be prevented by vitamin E, but the molecular mechanism involved is unclear. In this study, unlike ␥-tocopherol, the ␣-tocopherol vitamin E form was found to prevent 7-ketocholesterol-mediated apoptosis of A7R5 smooth muscle cells. To be operative, ␣-tocopherol needed to be added to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 35 publications
3
68
0
Order By: Relevance
“…The absence of typical apoptotic features in 24S-OHC-treated cells also supports the involvement of programmed necrosis. It has been known that oxysterols such as 7-ketocholesterol can induce apoptotic cell death through association with membrane lipid raft domains (15,32). We observed typical apoptotic features such as PS exposure and caspase activation in SH-SY5Y cells that were treated with 7-ketocholesterol (data not shown), suggesting that 7-ketocholesterol induces cell death via a different pathway with 24S-OHC.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The absence of typical apoptotic features in 24S-OHC-treated cells also supports the involvement of programmed necrosis. It has been known that oxysterols such as 7-ketocholesterol can induce apoptotic cell death through association with membrane lipid raft domains (15,32). We observed typical apoptotic features such as PS exposure and caspase activation in SH-SY5Y cells that were treated with 7-ketocholesterol (data not shown), suggesting that 7-ketocholesterol induces cell death via a different pathway with 24S-OHC.…”
Section: Discussionmentioning
confidence: 65%
“…It has also been shown that 24S-OHC acts as a ligand of the nuclear receptor liver X receptor, which regulates the gene expression of proteins involved in cholesterol transport in cell membrane (13). 7-Ketocholesterol, nonenzymatic oxidation product of cholesterol, has been shown to induce cell death through inactivation of the phosphatidylinositol 3-kinase/Akt signaling pathway (14), which is considered to be highly specific to lipid raft domains (15). 24S-OHC has been shown to possess potent neurotoxicity (16); however, the molecular mechanisms of the induction of neurotoxicity, particularly in the form of cell death, are less clearly defined.…”
mentioning
confidence: 99%
“…Our observations may therefore apply to a variety of proteins and different cell types. ␣ -Tocopherol, through its localization in membrane microdomains ( 43 ), may infl uence the function of microdomain-associated proteins via the same mechanism we propose for ␣ -tocopherol succinate. Indeed the ubiquity of this mechanism may help to explain the diverse and sometimes apparently contradictory actions which have been ascribed to vitamin E.…”
Section: Modulation Of the Mdp By ␣ -Tocopherol And ␣ -Tocopherol Sucmentioning
confidence: 52%
“…We hypothesize that the mechanism by which ␣ -tocopherol succinate infl uences P-gp is via its effect to decrease the dipole potential of membrane microdomains with which this receptor associates. In support of this notion, 7-ketocholesterol, an oxidized form of cholesterol known to localize in cholesterol-rich microdomains ( 42,43 ) and demonstrated to decrease the dipole potential of the plasma membrane, was also shown to infl uence the interaction of saquinavir with P-gp. The apparent differences in the extent to which ␣ -tocopherol succinate and 7-ketocholesterol infl uence both the dipole potential and P-gp are suggested to be due to differences in their heterogeneous lateral distribution within membranes and, in particular, their extent of colocalization with P-gp in microdomains.…”
Section: Modulation Of the Mdp By ␣ -Tocopherol And ␣ -Tocopherol Sucmentioning
confidence: 82%
“…This view, however, is not universally accepted and an association of a-tocopherol with lipid rafts has been recently described [11]. This association was observed for a-tocopherol but not for c-tocopherol.…”
Section: Cellular Effects and Signaling Of Vitamin Ementioning
confidence: 97%